De novo transcriptome sequencing of Rhododendron molle and identification of genes involved in the biosynthesis of secondary metabolites - Zhou, Guo-Lin; Zhu, Ping (BMC plant biology, 2020)
Rhododendron molle (Ericaceae) is a traditional Chinese medicinal plant, its flower and root have been widely used to treat rheumatism and relieve pain for thousands of years in China. Chemical studies have revealed that R. molle contains abundant secondary metabolites such as terpenoinds, flavonoids and lignans, some of which have exhibited various bioactivities including antioxidant, hypotension and analgesic activity. In spite of immense pharmaceutical importance, the mechanism underlying the biosynthesis of secondary metabolites remains unknown and the genomic information is unavailable. To gain molecular insight into this plant, especially on the information of pharmaceutically important secondary metabolites including grayanane diterpenoids, we conducted deep transcriptome sequencing for R. molle flower and root using the Illumina Hiseq platform. In total, 100,603 unigenes were generated through de novo assembly with mean length of 778 bp, 57.1% of these unigenes were annotated in public databases and 17,906 of those unigenes showed significant match in the KEGG database. Unigenes involved in the biosynthesis of secondary metabolites were annotated, including the TPSs and CYPs that were potentially responsible for the biosynthesis of grayanoids. Moreover, 3376 transcription factors and 10,828 simple sequence repeats (SSRs) were also identified. Additionally, we further performed differential gene expression (DEG) analysis of the flower and root transcriptome libraries and identified numerous genes that were specifically expressed or up-regulated in flower. To the best of our knowledge, this is the first time to generate and thoroughly analyze the transcriptome data of both R. molle flower and root. This study provided an important genetic resource which will shed light on elucidating various secondary metabolite biosynthetic pathways in R. molle, especially for those with medicinal value and allow for drug development in this plant.